Migration of Latin American Nikkei and Chinese Trainees to Japan - SALGADO-MENDOZA, Gloria Trinidad (Papeles de Población; Vol. 10 Núm. 41 (2004): Papeles de Población, 2017)
In this paper it is introduced the case of Japan immigration of Latin American Japanese descendants (Nikkei) and Chinese cursillistas. It is explored how the new migratory market is opening for Latin Americans and the competition of chinese labour introduced as cursillistas located in the small and médium enterprises (SME). It is reported some research results carried on in Japan, 2002. The increasing pattern of the entrance of this nonskilled labour suggests: a) SME competitiveness is based on low labour cost; b) the government is supporting actions to disguise cheap labor trough training programs, contributing to precarious working conditions for nikkeis. The Marshallian concept of citizenship allows us to perceive migration of workers as the pursue of the social right to work beyond national frontiers.